2022
DOI: 10.3390/foods11131897
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Approach for Fish Freshness Evaluation: Principle, Application and Challenges

Abstract: Affected by micro-organisms and endogenous enzymes, fish are highly perishable during storage, processing and transportation. Efficient evaluation of fish freshness to ensure consumer safety and reduce raw material losses has received an increasing amount of attention. Several of the conventional freshness assessment techniques have plenty of shortcomings, such as being destructive, time-consuming and laborious. Recently, various sensors and spectroscopic techniques have shown great potential due to rapid anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 103 publications
(104 reference statements)
1
2
0
Order By: Relevance
“…From the above results, it can be found that compared to packaging materials such as starch and chitosan, PVA has excellent physical properties and is a good choice for the preparation of freshness indicator labels. This is consistent with the findings of Zhang et al ( Zhang, Sun, Sang, Jia & Ou, 2022 ).…”
Section: Resultssupporting
confidence: 94%
“…From the above results, it can be found that compared to packaging materials such as starch and chitosan, PVA has excellent physical properties and is a good choice for the preparation of freshness indicator labels. This is consistent with the findings of Zhang et al ( Zhang, Sun, Sang, Jia & Ou, 2022 ).…”
Section: Resultssupporting
confidence: 94%
“…Freshness is very important when assessing the quality of fsh and fshery products [2]. It can be described by various indicators based on biochemical changes after slaughter, including the K value [3], total volatile basic nitrogen (TVB-N) [4,5], and thiobarbituric acid contents [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the final stage of bacterial spoilage, Hx is converted to xanthine, uric acid, and other circle cleavage end products [10,11]. The freshness index K is calculated as the ratio the concentrations of ATP metabolites concentrations (usually presented in µmol/L) [13]:…”
Section: Introductionmentioning
confidence: 99%